New possibilities of processing, preserving and presenting old prints developed with the applicability of the latest computer technologies - Konik, Alicja; Karlak, Weronika; Codogni-Łańcucka, Diana (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article describes the impact of information and communication technology on the accomplishment of most important tasks performed by Old Prints Department, namely inventorying, processing, and rendering resources available. In a chronological order, it discusses the process of introducing computer technology to old prints processing. Due to implementation of most recent information and communication technologies inventorying and book processing is carried out only in electronic form and book records can be seen in Wrocław University Library local database, in NUKAT Union Catalog and Meta Catalogs linked to it, as well as in HPB database run by the Consortium of European Research Libraries (CERL). Alongside to electronic catalog, users have access to the Department's resources via digitized card catalog (including 'photocatalog' with photocopies of title pages, microfilm database which allows to search through various categories, as well as via Digital Library of University of Wrocław (DLUWr) which offers access to circa 6.000 most valuable old prints digitized as a result of the Department's current activity and within the framework of realized projects. Through selection of multifaceted keywords precise access points to digitized materials are created, and because of the latest technological tools a graphic content of old prints is prepared in the way so as the illustrations contained in them gain the status of independent objects. High quality scans form a starting point to a long-lasting archivization and open the door for an in-depth processing of such material's content as e.g. watermarks, covers, and for increased searchability of a text after OCR conversion. It offers a prospect for future research and sets new challenges for the Department.
Keywords: planned digitization; provenance; graphic documents; meta catalog; ordered digitization; digitized card catalog; Dublin Core; dLibra system; watermarks; semantic web; full text search; Enrich; CERL; microfilm electronic catalog; photocatalog; covers; Viadrina; PLMET; MARC21; computer processing; point of access to content; old prints; Europeana; research virtual environment; digital humanities; metadata scheme; Succeed; Digital Library of University of Wrocław; HPB Database; NUKAT; electronic inventory; OCR